2023
DOI: 10.1111/1753-0407.13356
|View full text |Cite
|
Sign up to set email alerts
|

Fasting and refeeding triggers specific changes in bile acid profiles and gut microbiota

Abstract: Background: Bile acids (BAs) are closely related to nutrient supply and modified by gut microbiota. Gut microbiota perturbations shape BA composition, which further affects host metabolism. Methods:We investigated BA profiles in plasma, feces, and liver of mice fed ad libitum, fasted for 24 h, fasted for 24 h and then refed for 24 h using ultraperformance liquid chromatography coupled to tandem mass spectrometry.Gut microbiota was measured by 16S rRNA gene sequencing. Expressions of BA biosynthesis-related gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 74 publications
0
0
0
Order By: Relevance
“…Akkermansia was negatively correlated with plasma unconjugated primary and secondary bile acids and glucose levels but positively correlated with plasma conjugated secondary bile acids and faecal unconjugated forms of both bile acids. In contrast, Lactobacillus and Bifidobacterium were positively correlated with plasma levels of unconjugated primary bile acids and unconjugated secondary bile acids [57]. These results are supported by other authors who demonstrated the involvement of Lactobacillus and Bifidobacterium in bile acid metabolism, including deconjugation, via bile salt hydrolases or 7α-dehydroxylation [74].…”
Section: Studies Conducted On Healthy Animalssupporting
confidence: 77%
See 2 more Smart Citations
“…Akkermansia was negatively correlated with plasma unconjugated primary and secondary bile acids and glucose levels but positively correlated with plasma conjugated secondary bile acids and faecal unconjugated forms of both bile acids. In contrast, Lactobacillus and Bifidobacterium were positively correlated with plasma levels of unconjugated primary bile acids and unconjugated secondary bile acids [57]. These results are supported by other authors who demonstrated the involvement of Lactobacillus and Bifidobacterium in bile acid metabolism, including deconjugation, via bile salt hydrolases or 7α-dehydroxylation [74].…”
Section: Studies Conducted On Healthy Animalssupporting
confidence: 77%
“…The results obtained for the Akkermansia population are also heterogeneous. IF resulted in increased Akkermansia abundance in five studies, mainly comprising short-term IF [57,65,67,69,72], but at lower levels during long-term IF [65]. Similar inconsistencies are observed in studies that reported variations of other genera, such as Clostridium or Allobaculum [58,66].…”
Section: Studies Conducted On Different Animal Modelssupporting
confidence: 52%
See 1 more Smart Citation